AB0188 Systematic Analysis of the Oral Microbiome in Primary SjÖgren's Syndrome Suggest Enrichment of Distinct Microbes. (9th June 2015) - Sandhya, P.; Sharma, D.; Vellarikkal, S.K.; Surin, A.K.; Jayarajan, R.; Verma, A.; Dixit, V.; Sivasubbu, S.; Danda, D.; Scaria, V.
Abstract : Background: Dysbiosis has been hypothesized to play a role in the pathogenesis of autoimmune disease. Primary Sjögren's syndrome (pSS) is an autoimmune disease characterized by sicca symptoms resulting from salivary and lacrimal gland dysfunction. This could result in dysbiosis of oral cavity. At the same time, dysbiosis could also be hypothesized to have a causative role. Previous studies using culture dependent approaches have provided evidence for altered oral microflora in pSS. However culture dependent approaches have caveats which have been abrogated with the advent of culture independent methodologies. Objectives: To systematically evaluate the microbiome in the oral cavity in patients with pSS using a culture independent shotgun metagenome sequencing Methods: Cases included adult patients fulfilling criteria for pSS by American-European Consensus Group (AECG) 2002 or American College of Rheumatology (ACR) 2012 classification criteria, while controls included healthy volunteers. Neither cases nor controls had oral disease or other obvious co morbidities, recent antibiotic intake. Individuals who had chronic intake of alcohol and tobacco were excluded. Saliva was collected in sterile tubes with buffer. DNA was extracted using Qiagen DNA isolation kit. Libraries were prepared and sequenced on Illumina Hiseq 2500 (Illumina Inc, USA). Reads mapping to the Human reference genome (hg19) were tagged. Reads were further reference mapped to the core oral microbiome sequences available from the Human Oral Microbiome Database. The read counts were normalized for the input reads as well as the genome size of the organism. A fold change (FC) of >2 and p value <0.05 by Student's t-test was considered significant. Results: Oral microbiome of 13 pSS patients and 12 healthy controls were analysed. Organisms significantly enriched in pSS included the following (FC; p-value) Capnocytophaga (2.09; 0.01), Dialister (2.13; 0.02), Fusobacterium (2.84; 0.04), Helicobacter (4.83; 0.03), Streptococcus (3.33; 0.01) and Veilonella (3.82; 0.006) spp. A paucity of Pseudomonas (8.9;0.03) spp. was noted compared to controls. Conclusions: A distinct subset of organisms was enriched in the oral cavity of patients with pSS. This subset includes Capnocytophaga previously shown to be associated with the pathogenesis and T cell activation in pSS. References: Almståhl A, Kroneld U, Tarkowski A, Wikström M. Oral microbial flora in Sjögren's syndrome. J Rheumatol. 1999;26:110-4. Almståhl A, Wikström M, Kroneld U. Microflora in oral ecosystems in primary Sjögren's syndrome. J Rheumatol. 2001;28:1007-13. Szymula A, Rosenthal J, Szczerba BM, Bagavant H, Fu SM, Deshmukh US.T cell epitope mimicry between Sjögren's syndrome Antigen A (SSA)/Ro60 and oral, gut, skin and vaginal bacteria. Clin Immunol. 2014;152:1-9. Acknowledgements: Authors acknowledge colleagues at Department of Clinical Immunology and Rheumatology, CMC Vellore for help in recruiting volunteers for the study. Authors VS and SS acknowledge funding from CSIR, India through Grant OLP1105 (EMPOWER). Disclosure of Interest: None declared